Market conditions for circular bioeconomy in emerging economies - Taron, Avinandan; Bhandarkar, Supriya; Bodach, Susanne; Gebrezgabher, Solomie A. (International Water Management Institute (IWMI). CGIAR Initiative on Resilient Cities, 2024)
Emerging economies face mounting challenges of resource scarcity, increasing waste generation, and energy insecurity. Circular bioeconomy strategies focused on converting organic waste into biogas, compost, and treated wastewater offer a sustainable pathway to address these issues. Biogas adoption varies across regions; Southeast Asian countries like Thailand, Malaysia, and Indonesia are scaling production with government incentives, while India’s SATAT initiative aims to deploy 5,000 compressed bio-gas (CBG) plants by 2025. In Africa and Latin America, small-scale digesters have improved livelihoods but remain underutilized due to infrastructural, financial, and technical barriers. Compost markets are similarly constrained. Although countries like Sri Lanka, India, and Bangladesh have supportive policies, composting remains limited due to poor waste segregation, inconsistent product quality, and competition from subsidized chemical fertilizers. MENA countries have high compost potential, yet quality and market penetration remain weak. Wastewater reuse is most advanced in water-scarce MENA nations, where treated water supports irrigation and landscaping. However, South Asia and Latin America struggle with low treatment coverage and public resistance. Common barriers across RRR value chains include lack of market protection, low consumer awareness, weak institutional coordination, and limited technological capacity. Addressing these through integrated policies, investment in infrastructure, and behavior change interventions is essential for scaling circular bioeconomy solutions in the Global South.